1978-2023- ЖЫЛЛАР УШЫН НӨКИС ҚАЛАСЫНДА ШАҢ БОРАН БОЛҒАН КҮНЛЕР САНЫНЫҢ СТАТИСТИКАЛЫҚ АНАЛИЗИ - Тлеумуратова, Б.С.; Султашов, Р.Г.; Қобланов, Ж.Ж. (SCIENCE and SOCIETY, 2024)
Atmospheric dust pollution is a concern for the people of Nukus. The article analyzes the statistical data on dust storms observed at the Nukus hydrometeorological station, based on surface observations for the years 1978-2023.
Keywords: dust storms; database; frequency; intra-annual variation; days of dust storms; intra-day variation; duration; Nukus